2009
DOI: 10.1002/cne.22017
|View full text |Cite
|
Sign up to set email alerts
|

Efferent projections of thyrotropin‐releasing hormone‐synthesizing neurons residing in the anterior parvocellular subdivision of the hypothalamic paraventricular nucleus

Abstract: The anterior parvocellular subdivision of the PVN (aPVN) contains non-hypophysiotropic TRH neurons that are densely innervated by feeding-related neuronal groups of the hypothalamic arcuate nucleus. To determine how these TRH neurons are integrated within the brain, the major projection fields of this cell group was studied by anterograde and retrograde tract-tracing methods. Projection sites were identified by injection of the anterograde tracer Phaseolus vulgaris leuco-agglutinin (PHAL) into the aPVN, and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 70 publications
0
50
0
Order By: Relevance
“…In addition, we evaluated whether proTRH mRNA levels in the anterior PVN (aPVN) changed in a manner correlated with the hyperphagia of animals, since the peptide from this subcompartment has been implicated in feeding regulation (Wittmann et al 2009a, Alvarez-Salas et al 2012. To identify the functioning of the transduction pathway of leptin in adults, we also evaluated expression patterns of target genes of leptin signaling in the arcuate nucleus (ARC) and PVN, such as Lepr and Npy, which directly or indirectly affect PVN proTRH mRNA levels during fasting.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we evaluated whether proTRH mRNA levels in the anterior PVN (aPVN) changed in a manner correlated with the hyperphagia of animals, since the peptide from this subcompartment has been implicated in feeding regulation (Wittmann et al 2009a, Alvarez-Salas et al 2012. To identify the functioning of the transduction pathway of leptin in adults, we also evaluated expression patterns of target genes of leptin signaling in the arcuate nucleus (ARC) and PVN, such as Lepr and Npy, which directly or indirectly affect PVN proTRH mRNA levels during fasting.…”
Section: Introductionmentioning
confidence: 99%
“…As an icv injection of TRH in different animal species, reduces their food and liquid intake (Choi et al, 2002;Karydis & Tolis, 1998;Vijayan & McCann, 1977;Vogel et al, 1979), it has been proposed as an anorexigenic factor, which has been tested in ad libitum feeding animals, in those subjected to stress-induced eating models, and also in fasted and hungry animals during the re-feeding period (Horita, 1998;Morley & Levine, 1980;Steward et al, 2003;Suzuki et al, 1982;Vijayan & McCann, 1977). As mentioned, PVN TRHergic neurons express receptors for different feeding-regulating peptides synthesized in the ARC, such as NPY, AgRP, CART and -MSH; also for leptin (Ob-Rb) which suggests that the hormone has an indirect effect on TRH expression by acting on feeding-related synthesizing neurons of the ARC, but also has a direct action on PVN TRHergic cells (Wittmann et al, 2009). As TRHergic neurons of the anterior part of the PVN are known to have projections to the ARC, to dorsomedial and to ventromedial hypothalamic nuclei, it is likely that besides its role in energy homeostasis, motivational aspects related to food intake might also be under TRH control.…”
Section: Dehydration-induced Anorexiamentioning
confidence: 89%
“…Two of the major projection fields of aPVN TRH neurons are the ARC and the dorsomedial hypothalamus (DMH) (Morton et al, 2006;Wittmann et al, 2009) thus, it is possible that the observed anorectic effect of the icv administered TRH is mediated by neurons of that subdivision (Wittmann et al, 2009), but it awaits to be elucidated. Feeding-regulating role of TRH from the anterior part of the PVN TRH is also supported by studies showing an unaltered expression of the peptide in suckling rats (Sanchez et al, 2001) that are known to develop hyperphagia during lactation periods (Xu et al, 2009).…”
Section: Tshmentioning
confidence: 99%
See 2 more Smart Citations